2012
DOI: 10.1007/s13659-011-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Review on “Long-Dan”, one of the traditional Chinese medicinal herbs recorded in Chinese pharmacopoeia

Abstract: "Long-Dan" is an important traditional Chinese medicinal (TCM) herb used widely for the treatment of inflammation, hepatitis, rheumatism, cholecystitis, and tuberculosis. In the Chinese Pharmacopoeia, the roots and rhizomes of four species from the genus Gentiana (Gentianaceae) are recorded as the original materials of "Long-Dan", called Gentianae Radix et Rhizoma. The species included G. manshurica, G. scabra, G. triflora and G. rigescens, which are distributed in different areas of China. Though iridoid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Investigation of its phytochemistry demonstrated that several metabolites, including iridoid glycosides, flavonoids and triterpenoids, could be isolated from G . rigescens (Wang et al ., ). Additionally, eleven 2,3‐dihydroxyl benzoates (gentisides A–K) only detected in this species were potential candidates for the treatment of Alzheimer's disease (Gao et al ., , ).…”
Section: Introductionmentioning
confidence: 97%
“…Investigation of its phytochemistry demonstrated that several metabolites, including iridoid glycosides, flavonoids and triterpenoids, could be isolated from G . rigescens (Wang et al ., ). Additionally, eleven 2,3‐dihydroxyl benzoates (gentisides A–K) only detected in this species were potential candidates for the treatment of Alzheimer's disease (Gao et al ., , ).…”
Section: Introductionmentioning
confidence: 97%
“…In China, “Long-Dan” is typically used for protecting liver [1], and is commonly used for curing inflammation, hepatitis, rheumatism, cholecystitis and tuberculosis as a well-known traditional Chinese medicinal (TCM) herb [2]. While, “Qin-Jiao”, another important TCM herb for fighting rheumatism since ancient times in China, has been used as therapy for rheumatism, arthralgia, stroke, hemiplegia, pains, jaundice and infantile malnutrition [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Many Gentiana species have been employed as folk medicines to treat disease and maintain health since the ancient times in the word (Aberham et al, 2007;Cao and Wang, 2010;State Pharmacopoeia Commission, 2010;Wang et al, 2012;Yang, 1991;Yang et al, 2010). Among them, roots and rhizomes of G. scabra Bunge and G. rigescens Franch.…”
Section: Introductionmentioning
confidence: 99%
“…f. are the traditional Tibetan medicine to treat pneumonia and fever. Because of the remarkable medicinal functions, plants of the genus Gentiana have been a hot topic in phytochemistry and pharmacology since the 1960s and exhibited chemical diversity (Wang et al, 2012;Yang et al, 2010). Additionally, more research demonstrated this genus is a rich source of iridoids and phenols such as gentiopicroside, swertiamarin, loganic acid, sweroside and mangiferin, which are commonly regarded as major constituents and likely to responsible for the different therapeutic effect of these folk medicines (Chen et al, 2013b Ikeshiro andTomita, 2007;Kakuda et al, 2002;Ma et al, 1994;Xu et al, 2006Xu et al, , 2007Xu et al, , 2008Xu et al, , 2011Yang et al, 2012;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%